Improvement on the construction of nonbinary t-sEC/AUED codes - ZHANG Peng-cheng; FU Fang-wei (Tongxin xuebao)
A general construction for nonbinary t-sEC/AUED codes of length n with the magnitude error criterion was presented by Fu et al. When n?1 is a prime power, a improvement on the construction was given and it was shown that the lower bound from the new construction was better than the bounds given by Fu et al.